Chemical Product and Process Modeling (De Gruyter, 2006)
CPPM is the premier forum for theoretical and applied research on product and process modeling, simulation and optimization. The journal assembles the best papers from around the world and covers the gap between product and process. It brings together chemical engineering researchers, practitioners, and software developers in a new forum for the international modeling and simulation community.